2022
DOI: 10.1371/journal.pone.0276876
|View full text |Cite
|
Sign up to set email alerts
|

Toward developing a sustainability index for the Islamic Social Finance program: An empirical investigation

Abstract: Several previous studies state that the Islamic Social Finance program has not fully succeeded in creating prosperity, and there are no definite measurements to show the sustainability impact of the program. Thus, a measurement is needed to analyze various aspects in achieving the success and sustainability of Islamic social finance programs. This study developed an index for performance evaluation with an emphasis on the success and sustainability of the Islamic Social Finance program. The study used the Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…As evidence of collaborative endeavors in producing joint studies, Although 811 authors were considered in this study, Figure 10 shows only authors with at least two studies published and one cited. Finance (Hassan et al, 2021a;Hassan et al, 2021b;Herianingrum et al, 2022), the sustainability index , the nexus between Islamic social finance, human resources, governance, and poverty (Widiastuti, Prasetyo, et al, 2022), integration of sustainability in Islamic finance . At this point, it is important to mention that authors from this set of clusters carry out their research mainly in Asia and were mainly formed in 2022.…”
Section: Co-authorship Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As evidence of collaborative endeavors in producing joint studies, Although 811 authors were considered in this study, Figure 10 shows only authors with at least two studies published and one cited. Finance (Hassan et al, 2021a;Hassan et al, 2021b;Herianingrum et al, 2022), the sustainability index , the nexus between Islamic social finance, human resources, governance, and poverty (Widiastuti, Prasetyo, et al, 2022), integration of sustainability in Islamic finance . At this point, it is important to mention that authors from this set of clusters carry out their research mainly in Asia and were mainly formed in 2022.…”
Section: Co-authorship Analysismentioning
confidence: 99%
“…Among the most prominent of these is a group of clusters formed by Muneeza, Hassan, Beiki, Widiastuti, and Ascaray, the most relevant authors measured by published studies, as confirmed in Figure 4. The main topics addressed by this group of authors are mainly COVID‐19 and Islamic Social Finance (Hassan et al, 2021a; Hassan et al, 2021b; Herianingrum et al, 2022), the sustainability index (Widiastuti, Robani, et al, 2022), the nexus between Islamic social finance, human resources, governance, and poverty (Widiastuti, Prasetyo, et al, 2022), integration of sustainability in Islamic finance (Widiastuti, Robani, et al, 2022). At this point, it is important to mention that authors from this set of clusters carry out their research mainly in Asia and were mainly formed in 2022.…”
Section: Scientometric Analysismentioning
confidence: 99%
“…Islamic social finance is now starting to be relied upon as a source of funding for social and humanitarian purposes. Considering that Islamic social finance continues to grow, and is proven to be able to overcome various problems [6]. At the world level, Islamic social finance has become a new financial resource in overcoming various social and humanitarian issues such as hunger, poverty, and refugee problems.…”
Section: Introductionmentioning
confidence: 99%